2017
DOI: 10.1186/s12961-017-0274-9
|View full text |Cite
|
Sign up to set email alerts
|

Participatory monitoring and evaluation approaches that influence decision-making: lessons from a maternal and newborn study in Eastern Uganda

Abstract: BackgroundThe use of participatory monitoring and evaluation (M&E) approaches is important for guiding local decision-making, promoting the implementation of effective interventions and addressing emerging issues in the course of implementation. In this article, we explore how participatory M&E approaches helped to identify key design and implementation issues and how they influenced stakeholders’ decision-making in eastern Uganda.MethodThe data for this paper is drawn from a retrospective reflection of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…However, the authors emphasized the important role of facilitation in meetings between community members and health providers to balance their respective demands. 39 A similar finding was observed by Kananura et al, 41 who found improved engagement from the community and health services management staff in response to participatory monitoring processes designed to monitor implementation of an antenatal care project. Yet the process was only maintained in the presence of the project team, suggesting challenges exist in ensuring long-term sustainability.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…However, the authors emphasized the important role of facilitation in meetings between community members and health providers to balance their respective demands. 39 A similar finding was observed by Kananura et al, 41 who found improved engagement from the community and health services management staff in response to participatory monitoring processes designed to monitor implementation of an antenatal care project. Yet the process was only maintained in the presence of the project team, suggesting challenges exist in ensuring long-term sustainability.…”
Section: Resultssupporting
confidence: 70%
“…Leadership and the role of active engagement from senior management was highlighted across multiple included studies as a feature associated with strengthened M&E capacity and facilitating uptake at the local level. 33 , 34 , 38 , 40 , 41 The concept of leadership is itself nuanced and difficult to measure and is represented slightly differently in each of the studies. In the study by Holvoet and Inberg, 38 which compared Rwandan and Ugandan health systems, there was evidence demonstrating the role of leadership in both countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 In recent years, the district has also become the unit of intervention and strengthening for improving the quality and outcomes of maternal, neonatal and child health (MNCH) care. District-based methodologies addressing MNCH include data-driven "bottleneck analyses," developed and popularized by UNICEF; 2,3 formal district planning; 4,5 quality improvement cycles; 6 participatory action research; 7 mentoring and coaching; 8 citizen score cards and other forms of social accountability; 9 or some combination of these. 3,10,11 Initiatives to strengthen the district health system using these methodologies vary in their entry points and the extent of additional resources they mobilize, but all are fundamentally concerned with how to galvanize existing district players and improve the efficiency of resource use.…”
Section: Background and Rationalementioning
confidence: 99%